2017
DOI: 10.1007/s40596-017-0735-z
|View full text |Cite
|
Sign up to set email alerts
|

Building Provincial Mental Health Capacity in Primary Care: An Evaluation of a Project ECHO Mental Health Program

Abstract: This is the first study to report objective mental health outcomes related to Project ECHO. The results indicate high-participant retention is achievable, and provide preliminary evidence for increased knowledge and self-efficacy. These findings suggest this intervention may improve mental health management in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 18 publications
3
87
0
Order By: Relevance
“…Several care models from primary care may provide useful guidance in this regard. For example, Project ECHO utilizes expert‐led video conferences to provide advanced training of primary care providers in mental health treatment. Integrated behavioral health care models embed mental health providers of various levels directly into the primary care clinic environment .…”
Section: Discussionmentioning
confidence: 99%
“…Several care models from primary care may provide useful guidance in this regard. For example, Project ECHO utilizes expert‐led video conferences to provide advanced training of primary care providers in mental health treatment. Integrated behavioral health care models embed mental health providers of various levels directly into the primary care clinic environment .…”
Section: Discussionmentioning
confidence: 99%
“…The principle of Project Extension for Community Healthcare Outcomes (Project ECHO) is to de-monopolize specialized medical knowledge and expertise and to increase access to this specialized knowledge and expertise in rural and underserved areas through videoconferencing technology and case-based learning [35]. Psychiatry and addictions-focused ECHO programs seem to be effective in increasing primary care physicians' knowledge and selfefficacy and in potentially reducing feelings of isolation [36].…”
Section: Overcoming Challenges and Seeing The Opportunities Of Rural mentioning
confidence: 99%
“… 9 In addition, in a recent assessment of our ECHO Ontario Mental Health project outcomes, our team found that there was a significant improvement in pre-post knowledge of over 12% for participating primary care providers ( P < .001, d = 1.13). 10 …”
mentioning
confidence: 99%